2021
DOI: 10.3390/ani11082359
|View full text |Cite
|
Sign up to set email alerts
|

Affordability, Feasibility, and Accessibility: Companion Animal Guardians with (Dis)Abilities’ Access to Veterinary Medical and Behavioral Services during COVID-19

Abstract: The research aims to explore COVID-19 health and safety protocol impacts on companion animal guardians living with (dis)abilities relating to veterinary medical and behavioral service access. The COVID-19 global public health crisis has impacted almost all international communities; however, vulnerable and marginalized groups have been disproportionately affected. Within the human–companion animal domain, COVID-19-driven societal impacts (e.g., social, health, and economic) not only boomed with new companion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…For example, pet owners that struggled with transport prior to the pandemic often faced increased difficulties during the pandemic due to the use of shared transport and the increased risk of COVID-19 infection [ 62 ]. Similarly, pet owners with disabilities faced increased challenges accessing veterinary care due to exacerbated financial challenges, transportation difficulties and the use of curbside services [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pet owners that struggled with transport prior to the pandemic often faced increased difficulties during the pandemic due to the use of shared transport and the increased risk of COVID-19 infection [ 62 ]. Similarly, pet owners with disabilities faced increased challenges accessing veterinary care due to exacerbated financial challenges, transportation difficulties and the use of curbside services [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ikeuchi and colleagues highlight that during the COVID-19 pandemic, socially isolated older adults without dogs were more likely to report lower psychological health than their peers who have or have had a dog in their life ( 6 ). Furthermore, animals have been shown to positively impact how people react, cope, and recover from disaster situations ( 7 11 ). Consequently, current COVID-19-specific research reports increased pet guardianship ( 12 ) and confirms the various support roles of the animal within human-animal bonds ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of Canadian pet owners with (dis)abilities found that for some, their (dis)ability (e.g., sensory, cognitive or motor) posed a barrier to virtual or telephone consultations or commuting to veterinary clinics during the pandemic [ 86 ]. A number reported that the inability to accompany their animals into the veterinary hospital led to distress, and reduced their willingness to access veterinary care [ 86 ].…”
Section: Strengths and Limitationsmentioning
confidence: 99%